SIDE EFFECTS OF HYGIENE PRODUCTS IN HEALTHCARE WORKERS AND TEMPORARY WORK INCAPACITY DUE TO THE USE OF HYGIENE PRODUCTS - Nedeva, Marija; Paravina, Mirjana (Acta medicae Medianae, 2025)
When performing their duties, healthcare professionals encounter a large number of diseased people on a daily basis at their workplaces in healthcare clinics and hospitals. This requires a special code of conduct. Prevention of infections and cleanliness are imperative. This process may cause side effects from the use of hygiene products, which is evident in every analysis of skin diseases, allergic and occupational conditions in particular. There is always a number of healthcare workers with contact dermatitis and the most common etiological factors are soaps, detergents, cleaning agents, infectious agents, medicines and disinfectants. Diagnostics, prevention, treatment and occupational rehabilitation, and assessment of work capacity are implemented in all cases of those affected by occupational allergic contact dermatitis.
Keywords: healthcare workers, allergic contact dermatitis, hygiene products, work capacity